Pandemic Pastoral and Post-Pastoral Occasions in Poetry of the Covid-19 Crisis - Sarah Montin (Angles)
Why does the pastoral aesthetic, as well its many contemporary, prefixed versions (anti-pastoral, dark pastoral, post pastoral, etc.), feature so prominently in poetry written on and during the Covid-19 crisis? Taking this question as a starting point to critical exploration, this article analyses how the topical poetry written during the period of the first lockdown in Britain (March-June 2020) relied extensively on the classical literary convention to articulate the experience of the pandemic. Taking as corpus the poems featured in the “Write Where We Are Now” online anthology curated by Carol Ann Duffy in 2020, this paper analyses how using and subverting pastoral tropes and effects allowed poets to reflect upon one of the great catastrophes of the early 21th century, linking the trauma of mass death to contemporary questions on (eco)poetry and its relation to nature and the environment.